Pengembangan Media Pembelajaran Mituhu (Komik Pitutur Luhur) pada Kompetensi Dasar Menulis Dialog Siswa Kelas VII SMP Negeri 22 Semarang - Zahroh, Avella Itsna Fatimatuz; Kurniati, Endang; Fuadhiyah, Ucik (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2020)
The objectives of this pitutur luhur comic strip study development are (1) to analyze the needs of students and teachers towards mituhu learning media (pitutur luhur comics), (2) to describe prototypes of mituhu learning media (pitutur luhur comics), and (3) to describe the results of expert validation regarding mituhu learning media prototypes (pitutur luhur comics). The design of this research is research and development. The procedures of this study include (1) potential and problems, (2) data collection, (3) product design, (4) design validation, and (5) design revisions. The results of the study are (1) teachers and students of SMP N 22 Semarang need learning media to write dialogue in the form of pitutur luhur comics, (2) pitutur luhur comics consist of three stories namely Becik Ketitik Ala Ketara, Sapa Jujur Bakal Makmur, and Aja Dumeh, (3) the results of the material expert validation got an average value of 3.2 from a maximum value of 4 which means this comic according to the basic competencies to be achieved, the results of the media expert validation got an average value of 3.6 from a maximum value of 4 design meaningful in accordance with the rules of comic development.